Georg Mancelius’ principles of orthography: the first period (until 1631) - Vanags, Pēteris; Frīdenberga, Anna; Trumpa, Anta (Baltistica, 2023)
The article analyses the writing system used by the 17th-century Latvian author Georg Mancelius in his early works (parts of the Lutheran church handbook “Lettisch Vade mecum” published in 1631). It examines the spelling used and suggests dividing the orthographic principles as follows: a phonetic principle, a morphemic principle, a lexically traditional principle, a differentiating principle, a purely grammatical principle, and a lexical-grammatical principle. Only the phonetic principle was explicitly formulated by Mancelius himself; the others were deduced through data analysis.